Oxidative and pyrolytic decomposition of an evaporated stream of 2, 4, 6-tribromophenol over hematite: A prevailing scenario during thermal recycling of e-waste. (December 2022) - Ali, Labeeb; Shafi Kuttiyathil, Mohamed; Altarawneh, Mohammednoor
Graphical abstract: Highlights: The study investigates decomposition of 2, 4, 6-tribromophenol over hematite. Hematite is very effective in capturing emitted HBr under oxidative conditions. Oxidation of TBP over hematite produces brominated olefins. Hematite assumes a poor cracking capacity under pyrolytic conditions. Captured HBr converts Fe2 O3 into FeBr2 . Abstract: Brominated flame retardants (BFRs) constitute a major load in the polymeric fraction of e-waste. Degradation of BFRs-laden plastics over transition metal oxides is currently deployed as a mainstream strategy in the disposal and treatment of the non-metallic segment of e-waste. However, interaction of pyrolysis's products of BFRs with transition metal oxides is well-known to facilitate the formation of notorious pollutants. Despite recent progress to comprehend the germane chemistry of this interaction, several important pertinent aspects remain to be addressed. To fill in this gap, an integrated experimental and simulation account of the pyrolytic and oxidative decomposition of a gaseous stream of 2, 4, 6-tribromophenol (TBP) over hematite (Fe2 O3 ) has been reported herein. TBP is utilized as a model compounds of BFRs as their most common formulations include brominated phenolic rings. Overall, hematite entails a rather low cracking capacity under pyrolytic conditions. Analysis of condensate products indicates that oxidative degradation of a gaseous stream of TBP results mainly in the formation of brominated alkanes such as bromoethane and bromo-pentane. Likewise, Ion chromatography (IC) measurements disclosed a noticeable reduction in the concentrations of escaped HBr. Transformation of iron oxides into iron bromides (possibly in the form of FeBr2 ) during pyrolysis and combustion operations is evident through XRD measurements. Density functional theory (DFT) calculations map out important reactions pathways that operate in the initial degradation of the TBP molecule. From a broader perspective, outlined results shall be instrumental to precisely assess the effectiveness of using iron oxides in thermal catalytic recycling of e-waste and the likely emission of brominated toxicants.